Financial Distress Analysis of Plantation Stocks on the Indonesia Stock Exchange - Surono, Yunan; Lastari, Adria Wuri (DINASTI RESEARCH, 2024)
This research is to see the financial performance of companies using 5 models of analysis of potential financial distress, namely the first Altman Z score model, revision, modification, Springate and Zmijewski on plantation stock issuers as many as 11 out of 21 companies on the Indonesia Stock Exchange. This model of potential financial distress can be used in public and private companies with various company sizes, which will be useful for early detection of the company's financial performance and the sustainability of the company's operations in the future. This analysis of the calculation of potential financial distress uses the help of the Microsoft Excel program. The results of this study conclude that the issuers of company stocks that have good financial performance based on the potential for financial distress using the 5 models, namely issuers with LSIP and SMAR codes who have never experienced financial distress at all in the research period.